Pemanfaatan Sarana Prasarana Indoor dan Outdoor RAUDHATUL ATHFAL - Pancaningrum, Novita (THUFULA, 2018)
THE USE OF INDOOR AND OUTDOOR INFRASTRUCTURE MEASURES IN RAUDHATUL ATHFAL LEVEL. The purpose of this study was to find out what are the indoor and outdoor infrastructure, to find out what are the uses of indoor and outdoor infrastructure and to know the ability what can be developed with indoor and outdoor infrastructure. This study uses the Triangulation method, integrates Interviews, documents and Observations. The results of the study show that there are quite complete Indoor and Outdoor Infrastructure Facilities. The infrastructure is useful as an Educational Game Tool. The Educational GameTool develops cognitive abilities, Religious and Moral Values, fine and rough motoric physics, Art and Language.